Income Tax - An Overview of the Portuguese Situation - David, Fátima (2003)
Portuguese accounting regulation has undergone a significant change in the last year as result of the adaptation to European Union directives, to the statements of the International Accounting Standards Board (IASB) and the Financial Accounting Standards Board (FASB). In this paper, the authors describe the relationship, in general, between accounting and taxation and, in particular, between financial reporting and taxation, in Portugal, which were calculated independently until June of2001. Regression analysis ,was one of the steps used in the research methodology, which is a, statistical procedure for estimating mathematically the average relationship between the dependent and independent variables. In making these calculations the authors faced some problems that are presented and discussed. The availability and accessibility of the accounting data were the main difficulties faced, but the compilation involved assembling retrospective and prospective data to prepare the taxation report and procedure conduct to ascertain whether the assumptions and development were appropriate. The research design is a cross-sectional model, since 1994 to 1998 with observations distributed by Portuguese municipal concelho and district. Given these problems, the authors want with this research, based on the financial reporting of the Portuguese firms, to show how estimated regression models can improve future decisions in relation to income tax.